LOGICAL LEARNING ADVENTURES: NURTURING THE DEVELOPMENT OF LOGICAL THINKING IN PRESCHOOL CHILDREN - Oripova Nodima Khalilovna; Umurkulova Mastura Rakhmatullaevna (Western European Studies, 2024)
The pre-school age is the first period when the child enters social life and begins community relations in his life. The knowledge and skills formed during this period will serve as a foundation for the following youth periods. For this reason, the topic of forming a child's logical thinking during preschool education is relevant. This article analyzes the games, methods and tools that form the logical thinking of preschool children
Keywords: preschool education; logical thinking; social institution